Pengaruh Penggunaan Youtube Sebagai Media Pembelajaran Terhadap Tingkat Kreativitas Mahasiswa Ekonomi Di Universitas Negeri Medan - Hotman Siboro; Nurita Pasaribu; Rahel Hutahaean; Eva Situmorang; Haryadi Haryadi (Departement of Mathematics Education, 2024)
This study aims to analyze the impact of using YouTube as a learning medium on the creativity levels of economics students at Universitas Negeri Medan. In the digital era, YouTube has become a popular educational resource, offering diverse content that supports the learning process. Creativity is an essential competency for students to face challenges in a competitive business world. This research employs a survey method, collecting data through questionnaires distributed to students. Quantitative data analysis is conducted to identify the relationship between YouTube usage and creativity levels. The findings indicate that, although YouTube provides access to various information, no significant impact on enhancing student creativity was found. This highlights the need for active engagement in the learning process to stimulate creativity and provides recommendations for the development of more interactive and collaborative teaching methods. This research is expected to contribute to the advancement of higher education in Indonesia.